Religious Iconography in the Siete Partidas Manuscripts - Prádanos Fernández, Jorge (Eikón / Imago, 2023)
The set of manuscripts of the Siete Partidas produced in the Middle Ages testify the impact, importance, and relevance of this legal work in Castile and other peninsular kingdoms. This importance led to the commission of illuminated codices by relevant figures with images that illustrated the different laws or legal concepts and, at the same time, served as a way of ornamenting and dignifying these manuscripts. In this study the author analyses the presence of religious iconography in the codices of the Siete Partidas, classifying the most notorious religious iconographic themes, as well as possible parallels in other late medieval illuminated legal works.